PENGEMBANGAN MOTORIK HALUS ANAK USIA DINI MELALUI TEKNIK FINGER PAINTING - Dewi lutfiatul hoiroh; Prasetiya, Benny (LPPM IAD Probolinggo, 2023)
Abstract Physical Motor Learning is given at the kindergarten level, where we as teachers are required to develop children's physical motor skills supported by interesting and fun learning media, especially children's fine motor skills so that children get used to moving their fingers agilely. The research results show that Introducing children to coloring with their fingers by combining Finger Painting media can develop the agility of early childhood in ABA V Kindergarten. The impact of the research results is that finger painting is useful in developing children's fine motor skills, developing imagination by using this method of coloring. This research aims to improve the fine motor skills of young children through finger painting. The approach applied in this research is qualitative by collecting data through direct observation and documentary recording. Keyword : finger painting, fine motor skills, early childhood